Blanchot and the moving image : fascination and spectatorship - Watt, Calum (Moving image (Modern Humanities Research Association), 2017)
The French writer and philosopher Maurice Blanchot (1907-2003) was a notoriously reclusive figure who wrote that his life was entirely devoted to literature. Why then have filmmakers and writers on film found so much inspiration in Blanchot's work? Blanchot and the Moving Image explores a constellation of connections between Blanchot, film and film theory and draws lines of intellectual influence to show how Blanchot's thinking of literature find its way by a kind of displacement into contemporary philosophical approaches to cinema. Three case studies examining individual films - by Jean-Luc Godard, Béla Tarr and Gaspar Noé - draw out how Blanchot's complex notions of fascination and image can contribute to theories of spectatorship. The first book-length treatment of this theme, Blanchot and the Moving Image thus demonstrates the overlooked importance of Blanchot's work for understanding contemporary film and film theory.